Determinants of voluntary or coerced sexual debut among Black African female adolescents in Soweto, South Africa: Findings from The Birth to Twenty Plus cohort study - Nyemba, Dorothy Chiwoniso (Department of Public Health and Family Medicine, 2018)
Early sexual debut whether voluntary or coerced increases exposure to high risk sex which leads to unplanned pregnancy, sexually transmitted infections including HIV and reproductive heal th problems during adolescence. This study aim s to examine the risk factors for age of sexual debut, either voluntary or coerced among Black African female adolescents from the Birth to Twenty cohort study in Soweto, South Africa . Part A is the study protocol which outlines the rationale for conducting this study , study aim, research methodology, analysis plan and ethical considerations. Part B forms the literature review which gives a summary of the existing literature and provides context for the dissertation. The objectives of the literature review were to identify published literature on determinants of either voluntary or coerced sexual debut in adolescents and identify gaps for further research. Part C is the manuscript presenting the results and discussion on the implications of key findings. The results showed that there are many Black African female adolescents who are engaging in early sexual debut and there is prevalenc e of coerced sexual debut among adolescents of similar age. Socio-economic status and maternal education were found to be significantly associated with coerced sexual debut. There is a need for interventions to delay sexual debut among young female adolescents from low socio-economic backgrounds and lower maternal education.